GIP/GLP-1RA as adjunctive to automated insulin delivery in adults with Type 1 diabetes (the AID-JUNCT trial): Study protocol for a prospective, randomized, clinical trial - Maria Carolina Fragozo-Ramos; Gabriela Schenker; Matthias Hepprich; Jaime Gallo-Villegas; Thomas Züger; Jose Garcia-Tirado (PLoS ONE, 2025)
Background Glycemic control in type 1 diabetes (T1D) remains a challenge, with 20−30% of adults achieving an A1c target of <7%. Glucagon-like peptide 1 receptor agonist (GLP-1 RA) and dual glucose-dependent insulinotropic polypeptide (GIP) and GLP-1 RA (GIP/GLP-1 RA) have emerged as a promising therapy in T1D. Previous studies have shown that patients with T1D can significantly improve glycemic control while experiencing a reduction in insulin dose and body weight when long-acting GLP-1RAs or GIP/GLP-1RAs are added to insulin therapy. However, randomized controlled trials (RCT) are still insufficient. Methods This is a prospective, randomized, parallel-group, open-label, superiority-controlled design that evaluates the safety and efficacy of adding tirzepatide to insulin therapy in participants with T1D under automated insulin delivery (AID) control. We will enroll 42 participants aged 18–65 years with confirmed T1D diagnosis ≥12 months, currently on AID insulin therapy for at least three months, with A1C ≥ 6.5% and ≤ 10%, and BMI ≥ 23 kg/m 2 . Participants will be randomized in a 1:1 ratio to either tirzepatide with a target dosage of 5.0 mg (after titration) or standard of care (SoC) for 16 weeks. The primary endpoint is continuous glucose monitoring (CGM)-measured percent time spent between 3.9 and 10.0 mmol/L (TIR) from baseline to follow-up after 16 weeks of treatment. Secondary endpoints include: the CGM-measured change in 24/7 percent time >10.0 mmol/L, > 13.9 mmol/L, < 3.9 mmol/L, < 3.0 mmol/L. The exploratory endpoints include: the change in body mass index (BMI), liver steatosis (MASLD), and body composition. Safety outcomes include severe hypoglycemia, diabetic ketoacidosis (DKA), and refractory gastrointestinal side effects. Discussion This is the first prospective study to investigate the safety and efficacy of tirzepatide (GIP/GLP1-RAs) as an adjuvant therapy to AID in T1D. This study may contribute unique data to significantly improving glucose and cardio-metabolic outcomes, re-directing attention to further treatment in T1D beyond insulin therapies.